Oncoceratium amphidactylum n. gen. n. sp. (Monogenoidea: Gyrodactylidae) from Hoplosternum littorale (Hancock) (Siluriformes, Callichthyidae) from southeastern Brazil - Vianna, Rogério Tubino; Pelegrini, Larissa Sbeghen [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; de Azevedo, Rodney Kozlowiski; Abdallah, Vanessa Doro (Springer Nature, 2023)
Oncoceratium n. gen. is proposed to accommodate Oncoceratium amphidactylum n. gen. n. sp. (Monogenoidea, Gyrodactylidae). Although the proposed genus is monotypic, the differences presented in the diagnosis clearly establish it as distinct from species from other genera, such as Gyrodactylus von Nordmann, 1832 and especially those that occur exclusively in the Neotropical region. The new genus is diagnosed by the presence of a bulbous male copulatory organ, with one row of spinelets of similar sizes and shapes, while the only spine usually found in the gyrodactylids is absent or not differentiated; a haptor with anchors presenting points folded outwards, and superficial and deep roots continuous and indistinguishable; the absence of a deep bar; and hooks in two bilateral clusters of eight hooks. Oncoceratium amphidactylum n. gen. n. sp. is described from the tamboatá fish, Hoplosternum littorale (Hancock) (Callichthyidae), and is characterized by the presence of a pair of horn-shaped anchors with the point turned outwards, a superficial bar shield and absent deep bar, hooks disposed in bilateral lobes, and a MCO with no spine or with a row with large spinelets visible in place of the spine. In addition to the morphological features, distance analysis and Bayesian inference, based on 5.8s and partial ITS2, support placing the new species in a new genus, and not including it in a cluster of species of Gyrodactylus and near to Gyrodactyloides bychowskii Albova, 1948, Ieredactylus rivuli Schelkle et al., 2011 and Laminiscus gussevi (Bychowsky & Polyansky, 1953) Pálsson & Beverely-Burton, 1983.